Gambaran Pengetahuan Tentang Pencegahan COVID-19 pada Anak Usia Sekolah: Description Of Knowledge About COVID-19 Prevention In School-Age Children - Fiki Wijayanti Wijayanti; Natalia Devi Oktarina (Pro Health Jurnal Ilmiah Kesehatan, 2023)
School-age children have a higher risk of contracting COVID-19 due to a lack of knowledge about how to prevent it, besides that school-age children still like to play with friends their own age. Considering that children are individuals who are susceptible to contracting the disease, therefore knowledge about Covid-19 needs to be given to children to implement preventive behavior and reduce the number of Covid-19 diseases. School-age children have a higher risk of transmission of COVID-19 due to a lack of knowledge about how to prevent it, Besides that, school-age children still like to play with friends their age. In order to fight against an increase in COVID-19 cases, various preventive measures absolutely must be implemented, both by the government and the community. The purpose of this study was to describe the knowledge of Covid-19 prevention in school-age children at SD Solafide Ungaran. The method in this study is to use an analytic descriptive design. The sampling method uses total sampling. Respondents in the study were 85 school-age children who attended Solafide Elementary School in grades 4, 5, and 6. The research instrument used a questionnaire sent via Google form via zoom. The variable in this study is knowledge about preventing covid-19. Data analysis uses frequency distribution. The results of this study were that most of the knowledge the on prevention of COVID-19 in children and in the good category, namely 61 children (71.8%). Keywords: Children, Knowledge, Covid 19   ABSTRAK               Anak usia sekolah memiliki risiko yang lebih tinggi terhadap penularan COVID-19 karena minimnya pengetahuan tentang cara mencegahnya, disamping itu juga anak usia sekolah masih suka bermain dengan teman – teman seusianya. Mengingat anak merupakan individu yang rentang tertular penyakit maka dari itu pengetahuan tentang covid 19 perlu diberikan kepada anak untuk mewujudkan perilaku pencegahan dan menekan angka penyakit covid 19. Anak usia sekolah memiliki risiko yang lebih tinggi terhadap penularan COVID-19 karena minimnya pengetahuan tentang cara mencegahnya, disamping itu juga anak usia sekolah masih suka bermain dengan teman – teman seusianya. Guna melawan adanya peningkatan kasus COVID-19, maka berbagai tindakan preventif mutlak harus dilaksanakan, baik oleh pemerintah ataupun masyarakat. Tujuan dari penelitian ini adalah untuk mengetahui gambaran pengetahuan pencegahan covid 19 pada anak usia sekolah di SD Solafide Ungaran. Metode dalam penelitian ini adalah menggunakan desain deskriptif analitik. Metode pengambilan sampling menggunakan total sampling. Responden dalam penelitian adalah anak usia sekolah jumlah 85 anak yang bersekolah di SD solafide pada kelas 4,5 dan 6. Intrumen penelitian mengunakan kuesioner yang dikirim melalui google form melalui zoom. Variabel dalam penelitian ini adalah pengetahuan tentang pencegahan covid-19. Analisis data menggunakan distribusi frekuensi. Hasil dalam penelitian ini adalah sebagian besar pengetahuan pencegahan COVID 19 anak pada keategori baik yaitu 61 anak (71.8%). Kata kunci : Anak, Pengetahuan, Covid-19